Característica fermentativa y microbiana del ensilaje de pasto king grass morado, asociado con varias concentraciones de cascara de maracuyá, en la finca experimental la María, Mocache, 2012 - Párraga Méndez, Jixon Andrés (2013)
The objective was to evaluate the effect of different proportions of passion fruit peel on fermentation characteristics and microbial composition of grass silage King Grass Purple (PKGM). The crop is harvested at the 71 days, the passion fruit peel (CM) was added at levels of 0, 5 and 10% of the fresh weight of the forage. 3 treatments were used with three replications, with a total of 36 microsilos distributed in a completely randomized design; T1: PKGM CM + 0%, T2: PKGM + 5% CM; T3: PKGM + 10% CM and evaluated during 4 periods of fermentation (7, 14, 28 and 42 days). The variables evaluated were: microbial composition (bacteria, fungi and yeasts) and fermentation characteristics (pH and temperature). The results demonstrate that the process of silage by adding increasing passion fruit peel, had no effect on the variable population growth of bacteria, fungi and yeasts. The best aerobic stability was presented by T3 (4.27) in the first period of fermentation, the T1 (4.43, 4.40 and 4.82) had the best range in the second, third and fourth period of fermentation. However, the reported temperature equal (p> 0.05) between treatments, however, the T2 and T3 (27.33 ° C), were the treatments had a lower temperature, in the second period, T1, T2 and T3 (27.00 º C) indicated the lower range in the third quarter and fourth quarter, the T1 and T2 (24.33 and 23.33 ° C, respectively), the lowest temperature reported. We conclude that the process of ensiling fodder PKGM with the inclusion of the residue showed no change, therefore, was not a good choice for the fermentation and improve end product quality. Keywords: passion fruit peel, microsilos, King Grass grass purple.